Risk-Based Audit: Facing the Challenges of Analyzing Complex Financial Data - Eko Priyojadmiko; Asri Ady Bakri; Mesak Yandri Masela (Dhana, 2024)
Risk-based auditing is an approach that is increasingly being applied to analyze complex financial data. This study aims to explore the challenges faced by auditors in implementing risk-based auditing, particularly in relation to the analysis of increasingly structured and unstructured financial data. The method used in this study is Systematic Literature Review (SLR) to identify and analyze various literatures relevant to the topic. The results show that although risk-based auditing is effective in identifying and managing risks contained in financial statements, its implementation faces significant challenges. Some of the key challenges include limited technical skills of auditors and difficulties in managing data spread across multiple information systems. To overcome these issues, companies need to invest in appropriate technology and provide adequate training for audit teams. In addition, strong management support is also an important factor in the successful implementation of risk-based auditing. This study concludes that with the right strategy, risk-based auditing can help improve audit quality and reduce company risk, despite the challenges faced. With the optimal application of technology, the audit process can be carried out more efficiently and accurately in analyzing complex financial data.